The impact of genetically modified cowpea on yields, postharvest losses, and profitability in Nigeria: Findings from a cluster randomized controlled trial - Amare, Mulubrhan; Andam, Kwaw S.; Spielman, David J.; Bamiwuye, Temilolu; Zambrano, Patricia; Chambers, Judith A.; Fasoranti, Adetunji; Popoola, Olufemi (International Food Policy Research Institute, 2025)
We assess the impacts of a genetically modified pod borer-resistant (PBR) cowpea variety in Nigeria through a cluster randomized controlled trial conducted in two major cowpea-cultivating states. Our design allows us to examine the impacts of PBR cowpea with and without a package of complementary inputs (fertilizer and insecticides) and in comparison to farmers who received only a conventional improved cowpea variety. Results indicate that farmers who received and planted PBR cowpea experienced significant increases in yield (21 percent) and net margins (49 percent) compared to those growing the conventional variety, with larger gains observed among those provided with the inputs package. Analysis of heterogeneous effects indicates substantial variation in outcomes based on baseline characteristics such as household size, landholding, pest control practices, and wealth. Estimation of group average treatment effects and classification analysis using a causal machine learning approach identify plot size, pesticide use, and assets as key drivers of impact heterogeneity. Findings highlight the need for targeted dissemination strategies to realize the sizable benefits of PBR cowpea for small-scale, resource-constrained farmers.